MANAGEMENT OF INNOVATIVE DEVELOPMENT OF FOOD INDUSTRY ENTERPRISES IN RK - Seisenbina , A.A. (Academic Journal of Physical and Chemical Sciences, 2018)
Managing the innovative development of food industry enterprises in the Republic of Kazakhstan is a very relevant topic, since innovation is a system of measures to use scientific, scientific, technical and intellectual potentials to obtain new or improved products. From a financial point of view, this process can be viewed as investing, developing and distributing a newest product or service. In this case, it acts as an innovation project, considered as a special case of an investment project. In this connection, the introduction of innovations in the food industry is a major factor in improving the efficiency of enterprises. According to the authors, the introduction of scientific and technological advances into food production ensures the transition to the use of progressive technological processes.